2013
DOI: 10.53761/1.10.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Writing at the Graduate Level: Improving the Curriculum through Faculty Collaboration

Abstract: This article describes a collaborative self-study undertaken to identify the source of academic writing difficulties among graduate students and find ways to address them. Ten faculty members in a college of education came together to define the problem and to analyze data gleaned from faculty and student surveys, course documents, course assignments, and course assessments. We found discrepancies between faculty and student perceptions about graduate preparation for academic writing and between the espoused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Writing effectively in the scientific field calls on a wide range of skills, one of which is thinking critically (Bair & Mader, 2013). As one of their qualities, an individual capable of critical thinking will make an effort to locate information and sources that they know they can trust to be true (Zuchdi, 2009;Munandar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Writing effectively in the scientific field calls on a wide range of skills, one of which is thinking critically (Bair & Mader, 2013). As one of their qualities, an individual capable of critical thinking will make an effort to locate information and sources that they know they can trust to be true (Zuchdi, 2009;Munandar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In academic writing, students are required to connect ideas, concepts, and theories using advanced skills and applying "depth and breadth" learning (Lavelle & Bushrow, 2007). Although it is often assumed that postgraduate students have acquired strong academic writing skills prior to matriculation (Plakhotnik & Rocco, 2016), studies have shown that these students lack necessary skills such as proposal writing (McCarthy & Dempsey, 2017), evaluating and citing source material (Walter & Stouck, 2020), writing effective literature reviews (Bair & Mader, 2013), synthesizing theories and scientific works (Walter & Stouck, 2020), and familiarity with scientific scholarly conventions (Jeyaraj, 2020). Furthermore, basic academic writing skills such as mechanics, clarity, structure, and paragraph-building have been identified as additional weaknesses among L2 postgraduates (Keong & Mussa, 2015;Mehar Singh, 2019).…”
Section: Literature Review Academic Writing In Postgraduate Studymentioning
confidence: 99%
“…Academic writing is a general term that refers to the various forms and styles of rhetorical prose that are used for research communication in a variety of academic fields (Anderson & Cuesta-Medina, 2019) and widely identified as a crucial skill for students to improve their educational performance at university level (Sajid & Siddiqui, 2015). Thus, academic writing skills must be integrated throughout the graduate studies as a whole (Bair & Mader, 2013). For instance, academics write for a variety of reasons, extending from proposing new projects to sharing their research findings with larger academic community (Chakma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%